Diabetic Foot Spa Implementation in Early Neuropathy Diagnosis Based on Blood Glucose Levels, Foot Sensitivity and the Ankle Brachial Index in Patients with Diabetes Mellitus - Erika Martining Wardani; chilyatiz zahroh; nur ainiyah (Universitas Airlangga, 2019)
Introduction: Diabetes Mellitus (DM) is a cause of morbidity mainly due to vascular complications. The prevention of diabetic foot problems can be done through metabolic control and foot exercises. The purpose of this study was to determine the effect of diabetes foot spa measures on blood glucose levels, foot sensitivity and the ankle brachial index. Methods: This research was a pre-experimental design. The population totaled 170 DM patients and the sample was finalized at 30 respondents. The independent variable was diabetic foot spa, while the dependent variables were blood glucose levels, blood sensitivity and the ankle brachial index. The data was analyzed using a t-test and Wilcoxon rank test. Results: Diabetic foot spa in early neuropathy detection testing has a blood glucose level of t=9.523 and a p value=0.000. Diabetic foot spa also significantly affects foot sensitivity with a ρ <α (0.001<0.05) and an ankle brachial index of (ABI) ρ<α (0.008 < 0.05). Conclusion: Diabetic foot spa conducted regularly and independently can reduce the level of complications in Diabetes Mellitus patients. Furthermore, the tingling and pain in the feet can be reduced or even disappear as well as preventing complications such as foot ulcers that can often become amputations.